(untitled) (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2022)
The information technology and communications (IT&C) market for audio devices has increased in supply and demand in recent years. Wi-Fi, Bluetooth, or DECT technologies involve connectivity that contains an encryption protocol scheme that assures resistance to third-party interception. However, when discussing a secured transmission, we must look at the communication link. The audio end devices generate unintended emissions, which may contain information that can be eavesdropped on, a phenomenon that researchers in the specialty literature have studied. This paper aims to emphasize the wireless headphones’ vulnerability by analyzing their emission security breaches at several distances. Using specialized TEMPEST equipment, the vulnerability of two different headphone models is highlighted by successfully reconstructing pieces of information corresponding to three audio test patterns.